Tracking the activity-dependent diffusion of synaptic proteins using restricted photoconversion of Dendra2 - Cassé, Frédéric; MARTIN, Stéphane (Frontiers in Cellular Neuroscience, 2015)
Spines are small protrusions on dendritic membranes receiving inputs from axonal termini. They consist in a head connected to the dendritic shaft by a narrow neck and contain multiple synaptic actors that interact in a coordinated manner to allow for synaptic communication. This process involves many proteins that are moving in and out spines. However, comparing this synaptodendritic movement in basal and stimulated conditions is very challenging. Here we describe an elegant method to measure the activity-dependent diffusion of synaptic proteins using Dendra2 photoconversion. We provide a successful method to obtain Dendra2-photoconverted images and a step-by-step procedure to analyze the data. This live-imaging approach may also apply to investigate the diffusion of proteins across other subcellular compartments or organelles including but not restricted to, nucleus, nucleolus, ER or vesicular structures. Once the imaging system is set up, data can be acquired in 1-30 minutes and analyzed in approximately 1-4 hours.